ACTIVITY BASED COSTING DALAM PENENTUAN HARGA POKOK PRODUKSI - Ridwan, Nida Faradiba; Suherman, Acep (Balance : Jurnal Akuntansi dan Bisnis, 2021)
This study aims to determine the calculation of the cost of home construction production using the Activity Based Costing method. Because at this time it is known that the Company is using a traditional system. The cost of production is important because it can be used as a basis for decision making and affect the selling price. This research was conducted using qualitative descriptive methods. The data used are primary data and secondary data. Data collection through interviews, documentation, and literature study. The results of this study indicate the cost of production with the Activity Based Costing method provides cheaper results for the type of house 36/78. As for the type of house 40/91 and 45/104 get more expensive results. This difference is due to the fact that in calculating the cost of goods manufactured by the Company, only one cost driver is used. So, factory overhead costs are generalized to three types of houses. Whereas the Activity Based Costing method imposes different factory overhead costs for each product. Therefore, determining the cost of production is very important, with the Activity Based Costing method of decision making by management can be improved.